1997
DOI: 10.1007/s003470050214
|View full text |Cite
|
Sign up to set email alerts
|

Open foramen ovale in patients with arterial occlusions of the retina and optic nerve

Abstract: From our findings, it appears highly probable that ocular arterial occlusion is caused by paradoxical embolism. PFO should be taken into account in establishing a diagnosis, including diagnosis in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The frequency and significance of PFO in association with ocular circulatory disturbances were evaluated in forty patients with acute arterial occlusions of the posterior bulb segment through transthoracic and transesophageal echocardiography by Steuber and colleagues [16]. PFO was identified in nine patients and two of them showed that the potential source of paradoxical embolism was phlebothrombosis in their clinical history.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency and significance of PFO in association with ocular circulatory disturbances were evaluated in forty patients with acute arterial occlusions of the posterior bulb segment through transthoracic and transesophageal echocardiography by Steuber and colleagues [16]. PFO was identified in nine patients and two of them showed that the potential source of paradoxical embolism was phlebothrombosis in their clinical history.…”
Section: Discussionmentioning
confidence: 99%
“…This condition is caused by a venous embolus that crosses the PFO or that is trapped in PFO [4][5][6]. Brain arteries are the most frequent localization of paradoxical embolism [4]; less commonly paradoxical embolism has been described in the upper limb [1], coronary [8], renal or retinal arteries [9].…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxical embolism is frequently associated with cryptogenic stroke as well as peripheral embolism, brain abscess, and decompression sickness in underwater divers [ 4 ]. Other clinical manifestations of paradoxical embolus that have been described include myocardial infarction [ 5 ], renal infarction, and retina artery occlusion [ 6 ].…”
Section: Discussionmentioning
confidence: 99%